Determinants Of Unmet Need for Family Planning in A Developing Country: An Observational Cross-Sectional Study - Saima Nazir; Anshu Mittal; Bhupinder K Anand; RKD Goel; Jagjeet Singh; Arshad Rashid (Medsci Publications, 2015)
Background: Understanding the characteristics of women with unmet need can helpplanners strengthen the population control programs. The aim of this study was to assess the unmet need of contraception and its determinant factors. Methods: This observational cross-sectional study was carried out in urban and rural field practice areas of a medical college hospital in India over a period of one year and included 2000 married women. Data was collected using a pre-tested questionnaire during a face-to-face interview. Results: The overall unmet need for family planning was 7.5% (9.1% in rural area and 5.9% in urban area, P - value = 0.0002). Lowest unmet need was seen in the age group 15 - 19 years. Unmet need was higher in illiterate, unemployed women belonging to the low socio-economic group. Respondents whose husbands were illiterates or involved in menial jobs also had a higher unmet need. Unmet need was highest (11.6% rural, 10% urban) in the respondents having three or more children. Among reasons for not using contraception, family inhibition, scare of infertility, cost constraints and unhappiness with health services were significantly associated with unmet need. Conclusion: Education, income, occupation, knowledge about contraception, communication with partner regarding family planning, media accessibility, gender preference were identified as the contributing factors for Unmet Need.